Verjetnostni model računanja - Žerovnik, Janez (Informatica (Ljubljana), 1989)
In article a survey of a probabilistic model of computation is given. Some classes of probabilistic algorithms are defined. Preliminary sections give definition of classical (deterministic) model of computation and introduction to the theory of time complexity of computation.
Keywords: computer science; računalništvo; verjetnostni model računanja; hevristični algoritmi; časovna zahtevnost algoritmov